The impact of salesperson customer orientation on sales performance via mediating mechanism. Issue 5 (1st June 2015) - Singh, Rakesh; Venugopal, Pingali
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This study aims to address the need to study salesperson's customer orientation and its effectiveness to explain the efficacy of predispositions and skills at individual level. This study is set in the Indian context and, therefore, offers a detailed insight from an Indian sales force perspective. Also, this study introduces self-leadership into sales literature. Design/methodology/approach – A model was tested using survey data collected from salespeople within a print media company located in India. A structural equation model was used to test the hypotheses. Findings – The results suggest an interesting interplay between salesperson's customer orientation and his/her sales performance. The relationship between customer orientation is fully mediated by salesperson's emotion regulation ability and his/her salesmanship skills. Results support the role of natural rewards strategies as driver of individual level customer orientation which will be of great interest in future research in this area. Research limitations/implications – The research suggests that a salesperson's customer orientation relates positively with sales performance through two process variables – emotion regulation and salesmanship skills. Within an Indian sales force, individual salesperson's customer orientation is significantly influenced by his/her natural rewards strategies which have important implication for sales force recruitment. Moreover, sales training and other interventions targeted toward building salesmanship skills and emotion regulation abilities may actually enhance effectiveness of customer-oriented sales force. Theoretical and managerial applications are also discussed. Originality/value – This study extends the literature through its examination of an Indian sales force, the incorporation of self-leadership construct (natural rewards strategies) and its argument for an alternative approach toward salesperson's customer orientation effectiveness.